2000
DOI: 10.1055/s-2000-9026
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Studies of Esophageal Carcinosarcoma: Analyses of its Morphological Characteristics Using Endoscopic, Histological, and Immunohistochemical Procedures

Abstract: It is conceivable that the carcinomatous and sarcomatous components grow separately from the early stage of the tumors, and that the sarcomatous component forms a protruding tumor mass because it has abundant stroma positive for type IV collagen and laminin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 12 publications
(17 reference statements)
3
69
0
3
Order By: Relevance
“…Chino et al 77 also observed increased expression of p53 protein both in carcinoma associated with idiopathic achalasia and in dysplasia, suggesting that dysplastic alterations in patients with advanced achalasia may be related to increased risk of tumor development. These authors also detected loss of p16 protein expression, which together with p53 participates in cell cycle regulation in the invasive parts of the carcinoma and in situ carcinoma in relation to the areas with dysplasia, hyperplasia, and normal epithelium.…”
Section: Chagas Disease Megaesophagus and Its Association With Esophamentioning
confidence: 94%
“…Chino et al 77 also observed increased expression of p53 protein both in carcinoma associated with idiopathic achalasia and in dysplasia, suggesting that dysplastic alterations in patients with advanced achalasia may be related to increased risk of tumor development. These authors also detected loss of p16 protein expression, which together with p53 participates in cell cycle regulation in the invasive parts of the carcinoma and in situ carcinoma in relation to the areas with dysplasia, hyperplasia, and normal epithelium.…”
Section: Chagas Disease Megaesophagus and Its Association With Esophamentioning
confidence: 94%
“…The various terms in use reflect the uncertain pathogenesis of this tumor. 9 Chino et al 10 reported that the carcinomatous component was differentiated squamous cell carcinoma and the sarcomatous component was spindle cell carcinoma. Histological cell (so-called carcinosarcoma), in other words, the sarcomatous components are considered to result from metaplasia of carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of carcinoma in patients with achalasia has been reported to range from 1.5% to 3.7% [5][6][7][8], and some studies have shown that, on average, patients with achalasia at the time of the diagnosis of carcinoma were in their fifties, i.e., earlier than patients with a normal esophagus [9,10]. Chino et al reported that most cases of esophageal carcinoma associated with achalasia had advanced achalasia with a flask-or sigmoid-type and grade II or III esophageal dilatation on X-ray classification by an esophagogram [9].…”
Section: Discussionmentioning
confidence: 98%